Genetic variation of Anisoptera costata Korth in Tan Phu tropical forest, Dinh Quan district, Dong Nai province - Hien, Dang Phan; Duc, Nguyen Minh; Hong, Nguyen Phan Lan; Xuan, Bui Thi Tuyet; Duy, Vu Dinh; Tam, Nguyen Minh (Vietnam Journal of Biotechnology, 2021)
Anisoptera costata Korth, an endangered species is distributed in lowland tropical forests of southern Vietnam. Habitat loss and over-exploitation are the major reasons for threatening this species. Eight polymorphic microsatellite markers were used to analyze 64 adult trees from three A. costata populations in lowland tropical forests of Tan Phu, Dinh Quan district, Dong Nai Province in Southeast Vietnam to detect the effects of deforestation on gene flow and the differentiation among populations in lowland tropical forests. The results showed that all A. costata populations have the moderate levels of the genetic diversity within populations with mean values of observed and expected heterozygosities, 0.242 and 0.269, respectively, moderate genetic differentiation among A. costata populations (0.179), and indicating limited gene flow (Nm = 1.15). Analysis of molecular variance indicated high genetic variation within populations (64.68%) and indicating moderate genetic structure in A. costata in Tan Phu. Bayesian analysis detected two genetic lineages, cluster 1 including one population of Mieu Co Nam and cluster 2 including two populations, Thac Mai and Bau Nuoc. These results contribute understanding genetic diversity of A. costata in lowland forests of Southeastern Vietnam and will provide guidelines for conservation, management and resoration of the species.